Analisis Pengaruh Penanaman Modal Dalam Negeri (PMDN), Penanaman Modal Asing (PMA), Tenaga Kerja, Dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi (Studi Kasus Di Provinsi Kalimantan Barat) - Muhammad Nadiv Avilla; Yani Riyani; Merry Triani; Widodo Putro Suharto (CV. ITTC INDONESIA, 2026)
This study is motivated by the importance of economic growth as a key indicator of regional development success, which is influenced by various factors such as investment, labor, and government expenditure in West Kalimantan Province, where economic growth has shown fluctuating trends during the 2019–2023 period. The objective of this study is to analyze the effect of Domestic Investment (PMDN), Foreign Investment (PMA), labor, and government expenditure on economic growth. The objective of this study is to analyze the effect of Domestic Investment (PMDN), Foreign Investment (PMA), labor, and government expenditure on economic growth. This research employs a quantitative approach with a correlational design. The population consists of all regencies/cities in West Kalimantan Province, with a sample of 14 regions observed from 2019 to 2023, resulting in 70 panel data observations. The data used are secondary data obtained from the Central Statistics Agency (BPS) through documentation techniques. Data analysis is conducted using panel data regression with EViews software, including model selection tests (Chow, Hausman, and Lagrange Multiplier) and classical assumption tests. The results indicate that partially, PMDN (p=0.457), PMA (p=0.120), labor (p=0.549), and government expenditure (p=0.570) do not have a significant effect on economic growth. Simultaneously, all independent variables also show no significant influence (F=0.862; p=0.499). The coefficient of determination (R²) is 0.1213, meaning that only 12.13% of the variation in economic growth can be explained by the model. In conclusion, the examined variables are not sufficient to explain economic growth optimally, indicating the need for more effective policies and the inclusion of other variables such as human capital quality, infrastructure, and leading economic sectors to promote sustainable economic growth.